Efficacy of Dietary Supplements in Inflammatory Bowel Disease and Related Autoimmune Diseases - Jadhav, Priyanka (Nutrients, 2020)
The microbiome is an important contributor to a variety of fundamental aspects of human health, including host metabolism, infection, and the immune response. Gut dysbiosis has been identified as a contributor to the errant immune response in a variety of immune-mediated inflammatory diseases (IMIDs), such as inflammatory bowel disease (IBD), rheumatoid arthritis (RA), and psoriatic disease (psoriasis and psoriatic arthritis). Given this, probiotics and prebiotics have been investigated as therapeutic options in these disease states. In our review, we highlight the current evidence on prebiotics and probiotics as well as other supplements (such as fish oils, vitamin D, and curcumin) as therapies for IBD. Recommendations, however, regarding the specific use of such supplements in IBD have been lacking, particularly from professional societies, often due to study limitations related to small sample sizes and design heterogeneity. Hence, we additionally examine the literature on the use of prebiotics, probiotics, and other supplements in related IMIDs, namely RA and psoriasis/psoriatic arthritis, as these diseases share many approved therapeutic options with IBD. Based on these combined findings, we offer additional evidence that may help guide clinicians in their treatment of patients with IBD (and other IMIDs) and provide recommendations on potential next steps in therapeutic research in this area.